2019
DOI: 10.1111/asj.13255
|View full text |Cite
|
Sign up to set email alerts
|

Effects of berberine on the growth performance, antioxidative capacity and immune response to lipopolysaccharide challenge in broilers

Abstract: This study evaluated the effects of berberine on growth performance, immunity, haematological parameters, antioxidant capacity, and the expression of immune response‐related genes in lipopolysaccharide (LPS)‐challenged broilers. We assigned 120 one‐day‐old male broilers (Ross 308) to two treatment groups; each group included two subgroups, each of which included six replicates of five birds per replicate. The experiment used a 2 × 2 factorial arrangement with berberine treatment (0 or 60 mg/kg dietary) and cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 52 publications
2
22
0
Order By: Relevance
“…Previous studies demonstrated that berberine possesses various pharmacological activities and may treat different diseases, such as sepsis, inflammation, diabetes and cancer, by multiple mechanisms, e.g., halting cell cycle progression and triggering apoptosis (Chen et al, 2017;Hou et al, 2017;Zou et al, 2017). In cancer cells, berberine could induce apoptosis and inhibit the chemotherapyinduced repopulation by suppressing the arachidonic acid metabolic pathway Zhao et al, 2017), enhance chemosensitivity through dose-orchestrated AMPK signaling , and reverses hypoxia-induced chemoresistance through the inhibition of AMPK-HIF-1a , In addition, berberine also plays a role in the regulation of immune response, oxidant stress, tissue fibrosis, and autophagy with low side effects and good resistance, suggesting its clinical and research values (Yang et al, 2019). In this study, berberine alone or in combination with doxorubicin maintained the N1 neutrophil phenotype to prevent carcinogenesis and chemotherapeutic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that berberine possesses various pharmacological activities and may treat different diseases, such as sepsis, inflammation, diabetes and cancer, by multiple mechanisms, e.g., halting cell cycle progression and triggering apoptosis (Chen et al, 2017;Hou et al, 2017;Zou et al, 2017). In cancer cells, berberine could induce apoptosis and inhibit the chemotherapyinduced repopulation by suppressing the arachidonic acid metabolic pathway Zhao et al, 2017), enhance chemosensitivity through dose-orchestrated AMPK signaling , and reverses hypoxia-induced chemoresistance through the inhibition of AMPK-HIF-1a , In addition, berberine also plays a role in the regulation of immune response, oxidant stress, tissue fibrosis, and autophagy with low side effects and good resistance, suggesting its clinical and research values (Yang et al, 2019). In this study, berberine alone or in combination with doxorubicin maintained the N1 neutrophil phenotype to prevent carcinogenesis and chemotherapeutic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, results show that liver gene expression of proinflammatory cytokines was enhanced by LPS administration. Consistent with these results, Yang et al [33] found that liver gene expression of IL-6, TNF α, and iNOS was considerably higher in the LPS-treated group than in the unchallenged broilers. Notably, although CORT treatment alone did not induce inflammatory gene expression, it could exacerbate LPS-induced mRNA expression of NF-κB and its downstream proinflammatory cytokines, such as TNF-α and iNOS, in broilers.…”
Section: Discussionmentioning
confidence: 52%
“…As an important immune organ, the liver is a target for LPS, and is primarily affected by bacterial LPS [33,34]. In this study, results show that liver gene expression of proinflammatory cytokines was enhanced by LPS administration.…”
Section: Discussionmentioning
confidence: 54%
“…Effects of Chinese herbal medicines like coriander seed, Coptis chinensis , rosemary etc. on immunological index (IgM, IgG, and IgA) have been largely reported, which displayed improvements at different levels in the immunological index when adding herbs in diets ( Hosseinzadeh et al., 2014 , Alagawany and Abd El-Hack, 2015 , Yang et al., 2019 ). Nonetheless, little is known about the effects of M. oleifera products on immunological index in birds.…”
Section: Discussionmentioning
confidence: 99%